Excitation–contraction coupling of human induced pluripotent stem cell-derived cardiomyocytes - Kane, Christopher; Couch, Liam; Terracciano, Cesare M. N. (Frontiers in Cell and Developmental Biology, 2015)
Induced pluripotent stem cell-derived cardiomyocytes (iPSC-CMs) hold enormous potential in many fields of cardiovascular research. Overcoming many of the limitations of their embryonic counterparts, the application of iPSC-CMs ranges from facilitating investigation of familial cardiac disease and pharmacological toxicity screening to personalized medicine and autologous cardiac cell therapies. The main factor preventing the full realization of this potential is the limited maturity of iPSC-CMs, which display a number of substantial differences in comparison to adult cardiomyocytes. Excitation-contraction coupling, a fundamental property of cardiomyocytes, is often described in iPSC-CMs as being more analogous to neonatal than adult cardiomyocytes. With calcium handling linked, directly or indirectly, to almost all other properties of cardiomyocytes, a solid understanding of this process will be crucial to fully realizing the potential of this technology. Here we discuss the implications of differences in excitation-contraction coupling when considering the potential applications of iPSC-CMs in a number of areas as well as detailing the current understanding of this fundamental process in these cells.